Removal of Cr(VI) from Aqueous Solutions Using Biowastes: Tella Residue and Pea (Pisum sativum) Seed Shell - Abayneh Kebede; Kassim Kedir; Fekadu Melak; Tsegaye Girma Asere (The Scientific World Journal)
The wide use of chromium (Cr) in different industries led to the release of a considerable amount of Cr(VI) into water bodies. Exposure to Cr(VI) can cause diseases in humans and animals. Therefore, low-cost technology for Cr(VI) removal is required. In this study, the biowastes, “Tella” residue (TR) and Pea (Pisum sativum) seed shell (PSS), were evaluated for their Cr(VI) removal efficiency from aqueous solutions. The physicochemical properties of adsorbents were studied, and the adsorbents were further characterized using FTIR and XRD. Batch adsorption experiments have shown that the Cr(VI) uptake was pH-dependent and found to be effective in a wide range of pH values (pH 1 to 10) for PSS. The kinetics of Cr(VI) removal by the adsorbents was well expressed by the pseudo-second-order model. The experimental equilibrium adsorption data fitted well with Freundlich isotherm indicating multilayers adsorption. The estimated Cr(VI) adsorption capacities of TR and PSS were 15.6 mg/g and 8.5 mg/g, respectively. On top of this, the possibility of reusing adsorbents indicates the potential applicability of TR and PSS for the treatment of Cr(VI) contaminated water. Further study on the evaluation of the efficiency of the adsorbents using real chromium-contaminated wastewater is recommended.